Palearctic species of the genus Tephritis (Diptera, Tephritidae) associated with plants of the tribe Senecioneae (Asteraceae) - Korneyev, Severyn V.; Khaghaninia, Samad; Namin, Saeed Mohamadzade; Zarghani, Ebrahim (Zootaxa, 2015)
Tephritis arnicae (Linnaeus, 1758) from Europe was the hitherto only Palearctic species of the genus Tephritis known to infest flowerheads of asteraceous plants of the tribe Senecioneae. An additional species with similar biology, Tephritis arsenii, new species, recently discovered in Iran and Armenia is described. It is very similar to T. arnicae in the shape of the aculeus and spermathecae, as well as the wing with darkened anal lobe and abdominal tergites with black setulae, but differs from it by the white posterior orbital and notopleural setae, and also by details of the wing pattern. Larvae of T. arsenii feed in flowerheads of Doronicum dolichotrichum Cavill of the tribe Senecioneae (Asteraceae).